Phenyl–Pentafluorophenyl Interaction-Mediated Ir(C^N)2(N^N)-(Ni-Metallacycle) Dual Catalysis for Light-Driven C-S Cross-Coupling Synthesis - Jun-Feng Chen; Zhan-Xin Zhang; Jing Li; Sheng-Li Huang (Inorganics, 2025)
In many photocatalytic systems employing dual catalysts, researchers often focus primarily on the individual performance of each catalyst while overlooking potential inter-catalyst interactions. In this work, we have developed an efficient dual-catalytic system for C-S cross-coupling reactions, utilizing Ir(C^N)2(N^N) photosensitizers (PSs) in conjunction with Ni3Ce metallacycles. By incorporating specifically designed ligands, we established phenyl–pentafluorophenyl interaction between the photosensitizer and the Ni3Ce metallacycle. Comparative experiments revealed that systems featuring this interaction exhibited superior catalytic performance. Furthermore, transient fluorescence studies demonstrated that the phenyl–pentafluorophenyl interaction extends the lifetime of the excited state of the photosensitizer. The primary objective of this work is to provide some references and inspiration for the development of dual-catalytic systems.